ALISHER NAVOI IN THE CULTURAL FIELD OF RUSSIA'S PUSHKIN ERA: FIRST MENTIONS, TRANSLATION EXPERIENCES, AND ORIENTAL STUDIES CONTEXT - F. B. Valixadjaeva (International Journal of Literature and Language Studies, 2026)
The article revisits the early reception of Alisher Navoi in Russian cultural space during the Pushkin era. The study emphasizes that the first Russian encounters with Navoi were not full literary translations but rather scholarly references, descriptive notes, paraphrases and fragmentary renderings produced within the broader development of Oriental studies. The Pushkin era created a cultural atmosphere in which interest in Eastern literatures, translation and comparative literary thinking became particularly visible. The article argues that these early forms of reception prepared the ground for later academic translations and systematic studies of Navoi’s legacy.